Realistic fear of cervical cancer risk in Japan depending on birth year. Issue 7 (3rd July 2017) - Yagi, Asami; Ueda, Yutaka; Egawa-Takata, Tomomi; Tanaka, Yusuke; Nakae, Ruriko; Morimoto, Akiko; Terai, Yoshito; Ohmichi, Masahide; Ichimura, Tomoyuki; Sumi, Toshiyuki; Murata, Hiromi; Okada, Hidetaka; et al.
ABSTRACT: Objective : In Japan, the possible adverse events upon HPV vaccination was widely reported in the media. MHLW announced the suspension of aggressively encouraging HPV vaccination in 2013, and inoculation rate has sharply declined. The aim of the present study was estimation of future cervical cancer risk. Methods : The latest data on vaccination rate at each age in Sakai City were first investigated. The rate of experiencing sexual intercourse at the age of 12, 13, 14, 15, 16, 17 and throughout lifetime is assumed to be 0%, 1%, 2%, 5%, 15%, 25%, and 85% respectively. The cervical cancer risk was regarded to be proportional to the relative risk of HPV infection over the lifetime. The risk in those born in 1993 whom HPV vaccination was not available yet for was defined to be 1.0000. Results : The cumulative vaccination rates were 65.8% in those born in 1994, 72.7% in 1995, 72.8% in 1996, 75.7% in 1997, 75.0% in 1998, 66.8% in 1999, 4.1% in 2000, 1.5% in 2001, 0.1% in 2002, and 0.1% in 2003. The relative cervical cancer risk in those born in 1994–1999 was reduced to 0.56–0.70, however, the rate in those born in 2000–2003 was 0.98–1.0, almost the same risk as before introduction of the vaccine. Discussion : The cumulative initial vaccination rates were different by the year of birth. It is confirmed that the risk of future cervical cancer differs in accordance with the year of birth. For these females, cervical cancer screening should be recommended more strongly.